OPTIMALISASI PEMBELAJARAN AKIDAH BERBASIS TEKNOLOGI DI MASA PANDEMI - Indah Khairunnisa; Yazida Ichsan; Nikmatin Muyasaroh; M Muhyidin; Hafiz Atha Muhanna (Universitas Islam Sultan Agung, 2021)
Departing from the covid-19 pandemic that is hitting humans today, all sectors of life seem to be experiencing shocks, especially education. The learning process that should be carried out directly between teachers and students, has now been transferred to an online system. The existence of major changes in the current education system has forced teachers to mobilize all their potential as educators by teaching using technology. Especially faith education, teachers are required to be able to provide faith education to their students as in face-to-face learning in the past. This is of course a new responsibility for teachers. However, in this limited condition, the teacher's work will be greatly helped by the support from the parents who are always by their children's side. It is a joint task between teachers and parents in optimizing the process of creed education for students.Keywords: Creed, Technology, and Pandemic